2022
DOI: 10.1002/ldr.4204
|View full text |Cite
|
Sign up to set email alerts
|

Impact of crop establishment and residue management on soil properties and productivity in rice‐fallow ecosystems in India

Abstract: The degradation of agricultural land, both chemical and biological, is a big concern all over the world. Crop cultivation practices that are distinctive to each location have negative consequences for agricultural production. Therefore, there is an urgent need for better crop and soil management techniques. This experiment was conducted for 5 years (2016–2020) to identify the best crop establishment‐cum‐residue management (CERM) practices and suitable crops for succession after the rice harvest in rice‐fallow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Both CA and partial CA-based scenarios showed significantly higher SOC than farmers’ practice. The SOC content of soil in CA-based systems are less prone to loss due to lower soil disturbance and SOC gets protected within soil aggregates resulting in higher SOC ( Kumar et al, 2022b ). Higher available macro-nutrient (N, P and K) and micro-nutrient (Mn, Zn and Cu) under CA-based scenarios could be ascribed to nutrient mobilization and mineralization caused by higher microbial activity and presence of a more labile pool of carbon ( Naik et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both CA and partial CA-based scenarios showed significantly higher SOC than farmers’ practice. The SOC content of soil in CA-based systems are less prone to loss due to lower soil disturbance and SOC gets protected within soil aggregates resulting in higher SOC ( Kumar et al, 2022b ). Higher available macro-nutrient (N, P and K) and micro-nutrient (Mn, Zn and Cu) under CA-based scenarios could be ascribed to nutrient mobilization and mineralization caused by higher microbial activity and presence of a more labile pool of carbon ( Naik et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil binding through deep‐rooted cropping systems may facilitate soil structural stability and greenhouse gas sequestration. However, an agronomical study reported 20% increase in soil organic carbon stock after 6 years of crop establishment and their residue management (Kumar, Mishra, et al, 2022). The cultivation of diverse crops and applying microbial consortium has received the attention of many researchers as this can offer multiple services and resilience to ecosystems (Awasthi et al, 2014; Awasthi et al, 2017).…”
Section: Review Of Papers Published In This Issuementioning
confidence: 99%
“…Several CSA technologies can improve crop productivity and build resilience to the climatic changing risks for smallholder farmers of rice-fallow areas. This can be done by choosing short-duration high-yielding rice varieties that have fewer water requirements and are tolerant to abiotic stresses, direct-seeded rice crop establishment methods, retaining rice stubble for moisture conservation, and introducing short-duration varieties of oilseeds and pulses [14]. As ~15 M ha in South Asia remains fallow (uncultivated) after the rice harvest each year, there are great scopes to increasing the cropping intensity as well as overall system productivity, which will concurrently improve profitability and can be the instrument used to achieve food and nutritional security in the regions.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve self-sufficiency in oilseeds and pulses and to curtail the outflow of the foreign currency for import, short-duration high-yielding oilseeds (e.g., mustard, linseed, and safflower) and pulses (viz. chickpea, lentil, lathyrus, and field pea) may be grown in the rice-fallow system depending on the residual soil moisture and lifesaving irrigation [14]. Additionally, pulses facilitate soil health restoration by fixing atmospheric nitrogen (N) and adding crop biomass, which ultimately improves the soil organic C (SOC) status of the soil [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation